2020
DOI: 10.1038/s41467-020-18755-4
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ signaling synergizes with LRRK2 in neurons and microglia derived from human induced pluripotent stem cells

Abstract: Parkinson’s disease-associated kinase LRRK2 has been linked to IFN type II (IFN-γ) response in infections and to dopaminergic neuronal loss. However, whether and how LRRK2 synergizes with IFN-γ remains unclear. In this study, we employed dopaminergic neurons and microglia differentiated from patient-derived induced pluripotent stem cells carrying LRRK2 G2019S, the most common Parkinson’s disease-associated mutation. We show that IFN-γ enhances the LRRK2 G2019S-dependent negative regulation of AKT phosphorylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 78 publications
4
61
0
Order By: Relevance
“…In the current study, we describe the development of high-throughput and sensitive assays to quantify the levels and phosphorylation of LRRK2 and Rab10 and apply these assays to better understand how LRRK2 is regulated in cellular models and in human subjects that carry LRRK2 variants. Using these assays, we observed an approximately one and a half to two-fold increase in expression or kinase activity are modulated by inflammatory stimuli or lysosomal damage (26,27,42,43). We demonstrated that Rab10 phosphorylation was significantly increased in iPSCderived microglia following treatment with pharmacological agents that dissipate the endolysosomal pH gradient, providing support that lysosomal dysfunction can impact LRRK2 activity in human microglia and highlighting the potential of this model to better understand the mechanisms governing LRRK2 regulation.…”
Section: Discussionmentioning
confidence: 68%
“…In the current study, we describe the development of high-throughput and sensitive assays to quantify the levels and phosphorylation of LRRK2 and Rab10 and apply these assays to better understand how LRRK2 is regulated in cellular models and in human subjects that carry LRRK2 variants. Using these assays, we observed an approximately one and a half to two-fold increase in expression or kinase activity are modulated by inflammatory stimuli or lysosomal damage (26,27,42,43). We demonstrated that Rab10 phosphorylation was significantly increased in iPSCderived microglia following treatment with pharmacological agents that dissipate the endolysosomal pH gradient, providing support that lysosomal dysfunction can impact LRRK2 activity in human microglia and highlighting the potential of this model to better understand the mechanisms governing LRRK2 regulation.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, LRRK2 G2019S microglia had reduced levels of nuclear NF-kB, upon treatment with both LPS and IFN-γ, suggesting impaired inflammatory signaling mediated by this transcription factor. Moreover, when the supernatant from LPS-treated G2019S microglia was added to control or G2019S iPSC-derived neurons a shortening of the neurite length was observed [ 127 ]. Conversely, a study investigating the motility of iPSC-derived monocytes found that G2019S knock-in cells were less motile than wild type cells [ 128 ].…”
Section: Disease Modeling: Animal Models Patient-derived Ipsc Models and Cell-based 3d Models And Platformsmentioning
confidence: 99%
“…Further, human iPSC (hiPSC)-derived neuronal models have enhanced the understanding of the role of PD-causing mutations. For example, it has been proposed that LRRK2-G2019S results in dopaminergic neurodegeneration with its functional role in mRNA translation and calcium homeostasis [ 57 ], oxidative phosphorylation [ 58 ], mitochondrial DNA damage [ 55 ], interferon gamma (IFN-γ) signaling [ 59 ], neuritogenesis [ 60 ], phagosome maturation [ 61 ], and lysosomal tubulation and vesicle sorting [ 62 ]. Similarly, the roles of SNCA-A53T in axodendritic neuropathology [ 63 ], cellular bioenergetics [ 64 ], endoplasmic reticulum (ER)-to-Golgi complex trafficking [ 65 ], mitochondrial dysfunction, and neuronal apoptosis [ 66 ] have been suggested through rigorous exploration of hiPSC-derived models.…”
Section: Animal and Human In Vitro Models Of Pd And Parkinsonismmentioning
confidence: 99%